Phase separation in Ag–Ge–Se glasses - Piarristeguy, A. (2007)
Field emission-scanning electron microscopy (FE-SEM) and electric force microscopy (EFM) measurements were carried out on bulk Agx(Ge0.25Se0.75)100−x glasses with x = 5 and 15 at.%. The presence of chemical contrasts and electrical inhomogeneity throughout the samples indicated that the glasses were phase separated. Moreover it appears that while silver-rich nodules of ∼1 μm were embedded in a silver-poor connecting phase in the glass containing 5 at.% Ag, it was the opposite that occurred in the glass containing 15 at.% Ag. Such an inversion explains the large difference of seven orders of magnitude in the conductivity of the two glasses.